2012
DOI: 10.1051/0004-6361/201219566
|View full text |Cite
|
Sign up to set email alerts
|

Colours of minor bodies in the outer solar system

Abstract: We present an update of the visible and near-infrared colour database of Minor Bodies in the Outer Solar System (MBOSSes), which now includes over 2000 measurement epochs of 555 objects, extracted from over 100 articles. The list is fairly complete as of December 2011. The database is now large enough to enable any dataset with a large dispersion to be safely identified and rejected from the analysis. The selection method used is quite insensitive to individual outliers. Most of the rejected datasets were obse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
97
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(108 citation statements)
references
References 63 publications
(50 reference statements)
9
97
0
Order By: Relevance
“…5 in Hainaut et al 2012). Compared to the colours of other bodies, 2012 DR 30 is certainly "blue" when its B − V colour is considered (close to the solar value), while it shows colours closer to the population average in R − I, and especially in R − I.…”
Section: Colours and Visual Reflectancementioning
confidence: 99%
“…5 in Hainaut et al 2012). Compared to the colours of other bodies, 2012 DR 30 is certainly "blue" when its B − V colour is considered (close to the solar value), while it shows colours closer to the population average in R − I, and especially in R − I.…”
Section: Colours and Visual Reflectancementioning
confidence: 99%
“…The mean and range for each spectral type are shown in Figure 3. The Minor Bodies in the Outer Solar System (MBOSS; Hainaut et al 2012) database 14 indexes the reported colors for objects in outer solar system dynamical populations, including Jupiter Trojans, short-and long-period comets, Centaurs, and TNOs. Forty-seven objects in the MBOSS tabulation have measurements in comparable filters and of sufficiently high signal-to-noise ratio to provide comparison to our grJ measurements of 1I/'Oumuamua.…”
Section: I/'oumuamua In Context With the Colors Of The Minor Planetsmentioning
confidence: 99%
“…The classification of targets in the "TNOs are Cool" program within the Gladman et al (2008) framework is based on the list used by Minor Bodies in the Outer Solar System 2 data base (MBOSS-2, Hainaut et al 2012;and Ejeta, priv. comm.).…”
Section: Target Samplementioning
confidence: 99%